Respuesta :

For this case what we should do is take into account the following vectors:

[tex]z = (-1,5,3)\\y = (- 6.2, -1)[/tex]

We must find the following subtraction of vectors:

[tex]z-y = (- 1,5,3) - (- 6,2, -1)[/tex]

Subtracting component to component we have:

[tex]z-y = ((- 1 + 6), (5-2), (3 + 1))[/tex]

By writing we have:

[tex]z-y = (5,3,4)[/tex]

Then the module of the resulting vector is given by:

[tex]| z-y | = \sqrt {5 ^ 2 + 3 ^ 2 + 4 ^ 2}[/tex]

Rewriting we have:

[tex]| z-y | = \sqrt {50}\\ | z-y | = \sqrt {2 * 25}\\ | z-y | = 5\sqrt {2}[/tex]

Answer:

The module of the resulting vector is given by:

[tex]| z-y | = 5\sqrt {2}[/tex]

option B

ACCESS MORE